That's what friends are for ; New sons or nuissance ; Filing the gap [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles Fil-Am relationship and mental colonialism ; annual selection of SONS, UP Diliman College of Law; and NBI raid on Ana Araneta Ocampo who was charged as baby trafficker.
That's what friends are for (18 min.) -- New sons or nuissance (14 min.) -- Filing the gap (13 min.)
VHS.
Keywords: University of the Philippines (Diliman), College of Law. Solidarity of Neutral Students; Prostitution; Military bases, American -- Philippines; Adoption -- Corrupt practices -- Philippines; Philippines -- Colonial influence